2021
DOI: 10.1039/d0cp03258a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of polypyrrole composited with a low percentage of graphene nanofiller

Abstract: Low concentration of graphene (<5%) in graphene/polypyrrole composite makes it quite challenging to devise a theoretical model for such composites. Herein we present theoretical calculations for geometric electronic and optical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Even so, there are few reports about strategies for tuning energy levels of PPy. In particular, some examples on this aspect have considered the formation of composite materials [ 61 , 62 ], the insertion of substituents into the monomer [ 63 ], and the insertion of new dopants into the polymer [ 64 ]. However, as far as we know, there are no reports on variations in the HOMO level of PPy when adjusting the electrosynthesis potential.…”
Section: Resultsmentioning
confidence: 99%
“…Even so, there are few reports about strategies for tuning energy levels of PPy. In particular, some examples on this aspect have considered the formation of composite materials [ 61 , 62 ], the insertion of substituents into the monomer [ 63 ], and the insertion of new dopants into the polymer [ 64 ]. However, as far as we know, there are no reports on variations in the HOMO level of PPy when adjusting the electrosynthesis potential.…”
Section: Resultsmentioning
confidence: 99%
“…The composite showed high electrical conductivity, good thermal stability, and enhanced electrochemical properties. In [ 76 ], theoretical studies of graphene/conducting polymer composites were carried out, as a result of which it was shown that the p-stacking orientation is preferable for such structures. For sandwich complexes of oligopyrrole with graphene nanoribbons (with lower graphene concentrations), interaction energies were found, and excellent additivity was shown.…”
Section: Composite Materials Based On Conductive Polymersmentioning
confidence: 99%